Mentoring students & young people : a handbook of effective practice - Miller, Andrew, 1949- (Kogan Page ; Stylus Pub., 2002)
Used in a wide range of situations in education, the development of mentoring and mentoring schemes in education over the last few years has been dramatic. This handbook presents mentors and anyone working with young people with a guide to effective.